A selection of eleven plants used as traditional Polynesian cosmetics and their development potential as anti-aging ingredients, hair growth promoters and whitening products. (5th December 2019) - Hughes, Kristelle; Ho, Raimana; Butaud, Jean-François; Filaire, Edith; Ranouille, Edwige; Berthon, Jean-Yves; Raharivelomanana, Phila
Abstract: Ethnopharmacological relevance: In French Polynesia, embellishment of the hair and skin is an important cultural and everyday practice. Yet, little research has focused on traditional preparations used for beautification in this region and their potential development as innovative cosmetic ingredients. Aim of the study: In this present study we aim to assess and compile the ethnocosmetic potential of plants of French Polynesia to select and further study plants showing the most promise to be developed as anti-aging, anti-blemish and hair care products. Materials and methods: A literature analysis of plants of the IECIC list, present in French Polynesia was conducted. The most interesting plants from a cosmetic development standpoint were selected based on four main criteria, i.e. their traditional use in Polynesian cosmetic-related preparations, their biogeographical status, their phytochemistry of cosmetic interest, and lastly their availability and absence from the UICN list. Furthermore, a preliminary screening of antioxidant and anti-inflammatory activities was also performed on several extracts obtained. Results: Eleven plants were chosen, and a compilation of multidisciplinary data emphasized each selected plant's potentiality. Traditional allegations showed uses ranging from dermatology such as wound healing or anti-inflammatory properties, to hair growth promoting preparations or even skin ligthening ones. Preliminary screenings were useful in narrowing the number of extracts to study. Literature-based data associated to traditional uses depicted how the remaining plants and plant parts could be developed for targeted cosmetic applications. Conclusions: A prospective approach of plants used traditionally for cosmetic purposes in French Polynesia gave insight on their development potential when paired with the appropriate multidisciplinary data. The eleven plants presented show promise in being developed sustainably as natural anti-aging or hair care products and as skin brightening agents. Graphical abstract: Image 1